The UK oil and gas supply chains: An empirical analysis of adoption of sustainable measures and performance outcomes - Yusuf, Yahaya Y.; Gunasekaran, A.; Musa, Ahmed; El-Berishy, Nagham M.; Abubakar, Tijjani; Ambursa, Hafsat M. (International journal of production economics, 2013)
As the world shifts its emphasis from hydrocarbons to cleaner alternative sources of energy, the question of how oil and gas companies react to such a dynamic change has been of interest to academic and policy makers. Such a shift in demand is a result of both the on-going campaign against greenhouse gas (GHG) emissions and forecasts of future rapid depletion rate of hydrocarbon reserves. Although deposits are still vast, hydrocarbons are not renewable and the cost of extraction is rising mainly because of location complexities of viable reserves. Over the years, some research efforts have centred on the problems of possible depletion of oil reserves whilst others have been on how to reduce GHG emissions in the oil and gas supply chains with the view to achieving sustainability. It is in respect of the latter case that this paper examines the concept of sustainability, its essence and historical evolution as well as the depth and extent of its adoption and related benefits in the UK oil and gas supply chains. The paper reviews existing literature on the subject to generate an appropriate and adequate context for the analytical investigations that follow. Furthermore, data on sustainability and performance were collected from the UK oil and gas industry through survey by questionnaire. The statistical analysis of the data shows the impact of sustainability on the operational and business performance of the UK oil and gas supply chains. ► This paper examines the concept of sustainability, its essence and historical evolution. ► The paper explores depth and extent of adoption of sustainability measures and related benefits in the UK oil and gas supply chains. ► The paper provides empirical evidence of the impacts of sustainability performance of the UK oil and gas supply chains.